Trauma‐Related Guilt: Conceptual Development and Relationship With Posttraumatic Stress and Depressive Symptoms. Issue 2 (April 2015) - Browne, Kendall C.; Trim, Ryan S.; Myers, Ursula S.; Norman, Sonya B.
<x xml:space="preserve">Abstract</x> Despite high prevalence and concerning associated problems, little effort has been made to conceptualize the construct of posttraumatic guilt. This investigation examined the theoretical model of trauma‐related guilt proposed by Kubany and Watson (2003). This model hypothesizes that emotional and physical distress related to trauma memories partially mediates the relationship between guilt cognitions and posttraumatic guilt. Using path analysis, this investigation (a) empirically evaluated relationships hypothesized in Kubany and Watson's model, and (b) extended this conceptualization by evaluating models whereby guilt cognitions, distress, and posttraumatic guilt were related to posttraumatic stress disorder (PTSD) symptoms depression symptom severity. Participants were male U.S. Iraq and Afghanistan veterans (N = 149). Results yielded a significant indirect effect from guilt cognitions to posttraumatic guilt via distress, providing support for Kubany and Watson's model (β = .14). Findings suggested distress may be the strongest correlate of PTSD symptoms (β = .47) and depression symptoms (β = .40), and that guilt cognitions may serve to intensify the relationship between distress and posttraumatic psychopathology. Research is needed to evaluate whether distress specific to guilt cognitions operates differentially on posttraumatic guilt when compared to distress more broadly related to trauma memories.